WORK STRESS AMONG NURSES IN RURAL HOSPITAL - Ilkafah, Ilkafah; Andrianto, Rohmad; Susanto, Joko; Tyas, Anestasia Pangestu Mei; Harisa, Akbar (Journal of Vocational Nursing, 2023)
Introduction: Work stress is part of a work problem or negligence usually causes the safety of patients who experience fatigue to nurses in hospitals, stressed nurses usually cause injury to patients because nurses not focus on serving patients, are less friendly, often dizzy, and if the number of patients too much of it is one of the things that affect work stress. This study aims to determine the description of work stress on nurses at rural hospital in Lamongan. Methods: The study is a quantitative descriptive research design, using a questionnaire and distributed to 97 nurses who are on inclusion criteria. Results: The results of this study were divided into 3 codes which were low, moderate, and high and the results of the study showed that the indicators of psychological symptoms were 80 respondents with a percentage of 82.5% in the low category, while the moderate category was 17 respondents with a percentage of 17. .5%, for indicators of physical symptoms as many as 94 respondents with a percentage of 96.9% in the low category, while for the moderate category as many as 3 respondents with a percentage of 3.1% in the moderate category, for indicators of behavioral symptoms as many as 97 respondents with a percentage of 100, 0% is included in the low category. Conclusion: Most of the results of the research on nurses at RSUD Dr. Soegiri Lamongan low work stress with a percentage of 100.0% .